Implementation of Corporate Governansi in MSME - Murwaningsari, Etty; Darmawati, Deni; Sofie; Rachmawati, Sistya (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The purpose of community service is to help MSMEs to prepare financial reports, which are needed to apply for bank financing for capital acquisition and business development. And be able to understand good governance in MSMEs. As an effort to strengthen the participation of good MSME governance to empower individuals, groups and communities in the field of family welfare, especially in efforts to increase income and shared welfare. So that it can improve corporate governance in MSMEs through understanding and implementing the SIAPIK program to prepare financial reports. The methods used in implementing community service are counseling, training and mentoring through presentations of materials delivered by the community service team. The main topics of community service include training on cooperative governance. Then a discussion was held with participants guided by a moderator through face-to-face meetings. Feedback was carried out with a questionnaire filled out by all members of PMKM Prima Indonesia who participated in community service activities. The results of the evaluation of the implementation of community service both during face-to-face meetings and through questionnaires showed that community service participants expressed satisfaction with this activity, and the purpose of community service was achieved where participants felt they had received benefits in the form of increased knowledge, understanding of MSME governance.